2000
DOI: 10.1128/aac.44.3.763-766.2000
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Chelating Activity of Tetracyclines and Its Impact on the Susceptibility of Actinobacillus actinomycetemcomitans to These Antibiotics

Abstract: Three tetracyclines (tetracycline, doxycycline, and minocycline) were found to possess iron-chelating activity in a colorimetric siderophore assay. Determination of MICs indicated that the activity of doxycycline against the periodontopathogen Actinobacillus actinomycetemcomitans was only slightly influenced by the presence of an excess of iron that likely saturates the antibiotic. On the other hand, the MICs of doxycycline and minocycline were significantly lower for A. actinomycetemcomitans cultivated under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 28 publications
(22 reference statements)
1
62
0
Order By: Relevance
“…The reversal of the inhibition of growth obtained by doxycycline, tetracycline, rolitetracycline, and norfloxacin combined with FeCl 3 was weaker than that obtained with minocycline, oxytetracycline, and desferrioxamine. With the latter antibiotics, the IC 50 was not influenced by FeCl 3 at 500 to 1,000 M. Using a siderophore colorimetric assay, doxycycline and minocycline were found to have a strong ironchelating activity, whereas that of tetracycline was less pronounced (18). However, Grenier et al (18) found that the interaction between iron and doxycycline or tetracycline appears not to strongly affect the antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reversal of the inhibition of growth obtained by doxycycline, tetracycline, rolitetracycline, and norfloxacin combined with FeCl 3 was weaker than that obtained with minocycline, oxytetracycline, and desferrioxamine. With the latter antibiotics, the IC 50 was not influenced by FeCl 3 at 500 to 1,000 M. Using a siderophore colorimetric assay, doxycycline and minocycline were found to have a strong ironchelating activity, whereas that of tetracycline was less pronounced (18). However, Grenier et al (18) found that the interaction between iron and doxycycline or tetracycline appears not to strongly affect the antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…With the latter antibiotics, the IC 50 was not influenced by FeCl 3 at 500 to 1,000 M. Using a siderophore colorimetric assay, doxycycline and minocycline were found to have a strong ironchelating activity, whereas that of tetracycline was less pronounced (18). However, Grenier et al (18) found that the interaction between iron and doxycycline or tetracycline appears not to strongly affect the antibacterial activity. Miles and Maskell concluded that the complexing of tetracycline with iron in vivo did not affect the efficacy of tetracycline but, rather, diminished the iron-induced enhancement of the infection (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…In light of these data, a role of chemotherapy in the persistence of this important pathogen has been suggested. Recently, it has been shown that tetracyclines are iron scavengers (151). Iron deprivation induces the expression of several virulence-associated proteins in bacteria (224,243), and it is known that free iron is scarce during infection (409).…”
Section: Antibiotics As Effectors Of Bacterial Virulencementioning
confidence: 99%
“…3 It is also caused by the effective character of minocycline in eliminating the growth of negative gram periodontal pathogen, by the high concentration of gingival crevicular fluid (GCF), and by the slow release in the periodontal pocket. 13 Based on the comparison of the sample group using the application of gel in the fourth week and in the sixth week (Table 2) there was no significant difference among them. However, the decreasing of the pocket depth was bigger in the sixth week.…”
Section: Resultsmentioning
confidence: 99%